Delinquency Theories, Group Composition, Treatment Locus, and a Service-Research Model for 'Traditional' Social Work Agencies - Feldman, Ronald A. (1973)
Summary Rehabilitative endeavors within correctional institutions have failed because of overpopulation, high costs, labelling and stigmatization of inmates, low transferability of treatment changes to the outside community, and deviant peer group composition. Community treatment programs have fared little better because they also entail client stigmatization and typically are conducted within the context of deviant peer groups. Consequently, in order to enhance the rehabilitative potential of community treatment, subsequent efforts should be conducted within traditional agencies and within pro-social peer groups. The emphasis upon pro-social rehabilitation environments does not posit any particular assets and/or liabilities of a given socio-economic stratum, thus avoiding a major deficiency of many sociological theories of juvenile delinquency, viz., the tendency to derive particularized etiological and interventive principles from a generalized variable, that is, social class. Instead, our basic assumption is that both anti-social and pro-social environments are to be found within any social stratum, and that the latter ought to constitute the preferred loci for rehabilitative endeavors. A brief overview of major formulations concerning juvenile delinquency reveals at least minimum consonance between their basic assumptions and the proposals set forth here. Moreover, although the proposals envision a broad scale augmentation of rehabilitation resources the operational consequences for individual agencies and their members appear to be minimal. Forthcoming empirical data will permit specific detailed examination of the foregoing proposals. However, as additional agencies choose to adopt or reject them prior to accumulation of all the requisite data one might easily conduct a separate study of considerable merit, the subject of which would be innovation within social work institutions